2022
DOI: 10.3389/fped.2022.965275
|View full text |Cite
|
Sign up to set email alerts
|

Azygos vein preservation is feasible and beneficial in esophageal atresia with tracheoesophageal fistula: A meta-analysis of randomized controlled trials

Abstract: BackgroundEsophageal atresia (EA) with tracheoesophageal fistula (TEF) is a common congenital anomaly. It is still unknown whether azygos vein preservation will increase the difficulty or time of operation and reduce the quality of anastomosis. Thus, we conducted this meta-analysis to explore the puzzle.MethodsTwo researchers independently searched the databases. Randomized controlled trials were included if these studies applied thoracotomy to perform operations and compared the outcomes in patients with EA/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…They demonstrated that preserving the Azygos vein can reduce the incidence of anastomotic leakage compared to ligating it. In addition, they recommended evaluating other aspects, such as postoperative esophageal strictures, in accordance with our study [ 16 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…They demonstrated that preserving the Azygos vein can reduce the incidence of anastomotic leakage compared to ligating it. In addition, they recommended evaluating other aspects, such as postoperative esophageal strictures, in accordance with our study [ 16 ].…”
Section: Discussionmentioning
confidence: 71%
“…A meta-analysis conducted by Wang et al [ 16 ] provided compelling evidence regarding the safety and benefits of preserving the Azygos vein in patients with EA–TEF. They demonstrated that preserving the Azygos vein can reduce the incidence of anastomotic leakage compared to ligating it.…”
Section: Discussionmentioning
confidence: 99%